2006
DOI: 10.1002/bmc.582
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alkylamine additives on the sensitivity of detection for paclitaxel and docetaxel and analysis in plasma of paclitaxel by liquid chromatography–tandem mass spectrometry

Abstract: The formation of multiple molecular ions, especially due to sodium adduct ion formation, is commonly observed in electrospray mass spectrometry and may make reproducible and sensitive quantitation difficult. The objective of this work was to investigate the underlying mechanism involved in the suppression of multiple molecular ion formation and to improve the sensitivity of detection for the two anti-neoplastic agents paclitaxel and docetaxel. The results showed that alkylamine additives could significantly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Octylamine was particularly advantageous in improving the detectability of paclitaxel and docetaxel by about a factor of 4-5 down to about 0.5-1.0 ng mL −1 . (250) A similar enhancement was reported for a 3-benzothiepine compound TAK-778 using 1-hexylamine; interaction of the alkyl amine with the phosphoryl group was postulated. (251) Methylammonium acetate was effective in improving the MS sensitivity for simvastin and its hydroxy acid degradation product.…”
Section: Carbonyl Compounds and Carboxylic Acidssupporting
confidence: 59%
“…Octylamine was particularly advantageous in improving the detectability of paclitaxel and docetaxel by about a factor of 4-5 down to about 0.5-1.0 ng mL −1 . (250) A similar enhancement was reported for a 3-benzothiepine compound TAK-778 using 1-hexylamine; interaction of the alkyl amine with the phosphoryl group was postulated. (251) Methylammonium acetate was effective in improving the MS sensitivity for simvastin and its hydroxy acid degradation product.…”
Section: Carbonyl Compounds and Carboxylic Acidssupporting
confidence: 59%
“…One major molecular ion could be obtained with either dodecylamine/acetic acid (0.1 mM/0.1 mM) or acetic acid/sodium acetate (1.7 mM/20 M). Gao et al studied competition between the formation of [M + Na] + and [M + alkylamine + H] + including their binding sites and established a quantitation method for paclitaxel with LOD at 0.5 ng/mL [78].…”
Section: Alkylamine Adduct Ionsmentioning
confidence: 99%
“…6 Furthermore, Zhao et al, 7 Mortier et al, 2 and Karnes' group 8,9 reported the same usefulness of alkylamines for simvastatin, paclitaxel, and docetaxel, respectively. Teshima et al investigated an application of 1-alkylamines for quantitative analysis using LC/ESI-MS, [10][11][12] while other chemicals have been studied as well.…”
Section: Introductionmentioning
confidence: 93%